Lymphocyte reconstitution following autologous stem cell transplantation for progressive MS. Issue 1 (March 2017) - Cull, G; Hall, D; Fabis-Pedrini, MJ; Carroll, WM; Forster, L; Robins, F; Ghassemifar, R; Crosbie, C; Walters, S; James, I; Augustson, B; Kermode, AK
Background: Autologous stem cell transplantation (ASCT) for progressive multiple sclerosis (MS) may reset the immune repertoire. Objective: The objective of this paper is to analyse lymphocyte recovery in patients with progressive MS treated with ASCT. Methods: Patients with progressive MS not responding to conventional treatment underwent ASCT following conditioning with high-dose cyclophosphamide and antithymocyte globulin. Lymphocyte subset analysis was performed before ASCT and for two years following ASCT. Neurological function was assessed by the EDSS before ASCT and for three years post-ASCT. Results: CD4+ T-cells fell significantly post-transplant and did not return to baseline levels. Recent thymic emigrants and naïve T-cells fell sharply post-transplant but returned to baseline by nine months and twelve months, respectively. T-regulatory cells declined post-transplant and did not return to baseline levels. Th1 and Th2 cells did not change significantly while Th17 cells fell post-transplant but recovered to baseline by six months. Neurological function remained stable in the majority of patients. Progression-free survival was 69% at three years. Conclusion: This study demonstrates major changes in the composition of lymphocyte subsets following ASCT for progressive MS. In particular, ablation and subsequent recovery of thymic output is consistent with the concept that ASCT can reset the immune repertoire in MS patients.